2015
DOI: 10.1177/1687814015592603
|View full text |Cite
|
Sign up to set email alerts
|

Study on double-shaft mixing paddle undergoing planetary motion in the laminar flow mixing system

Abstract: This article has studied the impact of double-shaft mixing paddle undergoing planetary motion on laminar flow mixing system using flow field visualization experiment and computational fluid dynamics simulation. Digital image processing was conducted to analyze the mixing efficiency of mixing paddle in co-rotating and counter-rotating modes. It was found that the double-shaft mixing paddle undergoing planetary motion would not produce the isolated mixing regions in the laminar flow mixing system, and its mixing… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 7 publications
(10 citation statements)
references
References 25 publications
0
10
0
Order By: Relevance
“…Similarly, [41] studied "the impact of double shaft mixing paddle undergoing planetary motion on laminar flow mixing system using flow field visualization experiments and computational fluid dynamics simulation. Digital image processing was conducted to analyze the mixing efficiency of mixing paddle in co-rotating and counter rotating modes.…”
Section: Type I -Mixer With Onementioning
confidence: 99%
“…Similarly, [41] studied "the impact of double shaft mixing paddle undergoing planetary motion on laminar flow mixing system using flow field visualization experiments and computational fluid dynamics simulation. Digital image processing was conducted to analyze the mixing efficiency of mixing paddle in co-rotating and counter rotating modes.…”
Section: Type I -Mixer With Onementioning
confidence: 99%
“…Therefore, researchers still continue to redesign the stirrer blade in order to obtain efficient systems in terms of energy, mixing time, and product quality. [1][2][3][4] Recently, many researchers focus on the performance of impellers with curved blades, and some works have been achieved using this type of impellers to study the flow pattern generated with rheological complex fluids. [5][6][7][8][9][10][11][12][13] Other researchers interested to Newtonian fluids with curved blade impellers in single or dual arrangements.…”
Section: Introductionmentioning
confidence: 99%
“…Yi, P. X. et al 1 via CFD method concluded that the geometric parameter, for example the clearance, plays a great role on the dispersive mixing efficiency, and the reasonable design of clearance can improve the mixing efficiency of the mixer. Zhang, J. Q. et al 2 obtained that inside the mixing vessel of the twin-blade planetary mixer, the alternative variation of the axial velocity, the tangential velocity and the radial velocity promote the convecting mixing of different compositions. Devals, C. et al 3 and Fradette, L. et al 4 found that decreasing the clearance increasing the shear rate and the power consumption, however, decreasing the bottom recirculation of the fluid flow.…”
Section: Introductionmentioning
confidence: 99%